TUBERCULOSIS CONTROL: CURRENT STATUS, CHALLENGES AND BARRIERS AHEAD IN 22 HIGH ENDEMIC COUNTRIES - Ibrahim, M Khan; Khan, Samreen; Laaser, Ulrich (Journal of Ayub Medical College Abbottabad, 2002)
Background: Despite the fact that Directly Observed Treatment Strategy (DOTS) short course is cost effective and universally recommended by WHO for effective TB control, it is beyond the financial reach of several highly endemic countries. This article aims at identifying barriers in DOTS’s implementation and progress in 22 high burden countries (HBCs) from TB. Methods: Medline abstracts, published papers and WHO reports were retrieved, critically examined and compared keeping standard parameters of TB control in view. Results & Conclusion: The increasing caseload, morbidity and mortality due to TB in high burden countries have become a major health challenge and threat to the health systems. The escalated burden of disease and deaths due to TB has posed a great threat to the international security. In the last decade little progress has been witnessed in the implementation of WHO’s recommended strategy called DOTS in the 22 high burden countries. Afghanistan, Pakistan, India, Brazil, Zimbabwe, S. Africa and Uganda are some of the countries still facing challenges in the effective introduction, implementation and expansion of DOTS. Financial inabilities contribute greatly to the failure of respective national TB control programs. High burden countries are usually in the economic recession or passing through severe socio-political turmoil that has further reduced spending on TB control. Majority depends on the international assistance and put little domestic efforts. Coupled with the lack of political commitment to the issue of TB control, authors urge high TB control Program managers in HBCs to increase spending and pay a great deal of commitment to the universal implementation of DOTS, increase case detection and case management to attain their global targets. Key words: DOTS, TB control, high burden countries.